Since \( JL \) is the perpendicular bisector of segment \( KM \), it implies that \( KH \) is equal to \( HM \). Thus, we can set the two expressions for the lengths of \( KH \) and \( HM \) equal to each other:
\[ KH = HM \]
Substituting the given expressions:
\[ 6y + 3 = 2y + 7 \]
Now, to solve for \( y \), we will first subtract \( 2y \) from both sides:
\[ 6y - 2y + 3 = 7 \]
This simplifies to:
\[ 4y + 3 = 7 \]
Next, we will subtract 3 from both sides:
\[ 4y = 4 \]
Now, divide both sides by 4:
\[ y = 1 \]
Now that we have \( y \), we can find the length of segment \( HM \) using the expression for \( HM \):
\[ HM = 2y + 7 \]
Substituting \( y = 1 \):
\[ HM = 2(1) + 7 = 2 + 7 = 9 \]
Thus, the length of segment \( HM \) is \( \boxed{9} \) units.